2020
DOI: 10.3390/cells9030730
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adipose Expression of Interferon Regulatory Factor (IRF)-5 Associates with the Signatures of Metabolic Inflammation in Diabetic Obese Patients

Abstract: Interferon regulatory factors (IRFs) are emerging as the metabolic transcriptional regulators in obesity/type-2 diabetes (T2D). IRF5 is implicated with macrophage polarization toward the inflammatory M1-phenotype, nonetheless, changes in the adipose expression of IRF5 in T2D and relationship of these changes with other markers of adipose inflammation remain unclear. Therefore, we determined the IRF5 gene expression in subcutaneous adipose tissue samples from 46 T2D patients including 35 obese (Body Mass Index/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…First of all, we show that the expression of immune-metabolic transcriptional regulator IRF5 was found to be significantly upregulated in monocytes from diabetic patients compared to nondiabetic individuals and that these changes associated with the expression of hyperglycemia-induced clinical marker HbA1c and several inflammatory markers including TNF-α, IL-1β, and CCR2. These data are corroborated, at least in part, by our previous reports showing enhanced subcutaneous-adipose tissue IRF5 expression in individuals with obesity and/or T2D in association with an inflammatory immune profile in the adipose tissue as well as by the data showing that macrophages and not adipocytes were the IRF5 expressors [ 13 , 14 ]. In line with this, at least in part, an earlier study by Dalmas et al also reported that IRF5 is the orchestral conductor of macrophage/lymphocyte activation in obesity and is involved in the crosstalk between inflammatory and prodiabetogenic factors.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…First of all, we show that the expression of immune-metabolic transcriptional regulator IRF5 was found to be significantly upregulated in monocytes from diabetic patients compared to nondiabetic individuals and that these changes associated with the expression of hyperglycemia-induced clinical marker HbA1c and several inflammatory markers including TNF-α, IL-1β, and CCR2. These data are corroborated, at least in part, by our previous reports showing enhanced subcutaneous-adipose tissue IRF5 expression in individuals with obesity and/or T2D in association with an inflammatory immune profile in the adipose tissue as well as by the data showing that macrophages and not adipocytes were the IRF5 expressors [ 13 , 14 ]. In line with this, at least in part, an earlier study by Dalmas et al also reported that IRF5 is the orchestral conductor of macrophage/lymphocyte activation in obesity and is involved in the crosstalk between inflammatory and prodiabetogenic factors.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we showed that adipose IRF5 expression was higher in obese individuals compared to lean and overweight, which was found to associate with several metabolic and inflammatory markers [ 13 , 14 ]. We further showed by confocal microscopy that the adipose tissue macrophages and not the adipocytes expressed IRF5 transcripts [ 13 , 14 ]. In line with these observations, first, we show that, in our T2D patient cohort, adipose IRF5 gene expression was significantly higher than their nondiabetic counterparts ( p = 0.006, Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the conditions were established, all slides were analyzed using the same parameters. The resulting color markup of the analysis was confirmed for each slide 59,61 .…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Relative gene expression to control, lean AT, was calculated using comparative Ct method as we previously described 56,58,59 . Results were normalized to GAPDH, and averages ± standard error of the mean (SEM) are shown relative to controls as indicated 60 .…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chaimentioning
confidence: 99%